A política pública de progressão continuada no ciclo de alfabetização: estudo em uma escola pública da rede estadual de Santa Maria/RS - Venturini, Alessandra (2017)
The objective of the present paper is to analyze the literacy process of the third year students of Elementary School of the Escola Estadual de Educação Básica Augusto Ruschi, located in the municipality of Santa Maria/RS, considering the system of Continued Progression in the year 2015 and the reflexes of the implementation of this Public Policy. In order to carry out this work, we opted for the quantitative-qualitative approach, with a case study, because it is the specific study of a context, a school of the state public network, using: Yin (2001), Gil (1995), Chizzotti (2006) and Ventura (2007). Initially, there were readings and reflections with authors, whose works make a historical recovery of education related to the regime of Continued Progression as a public policy and concepts of literacy, as well as, official documents: Federal Constitution (1988), LDBEN nº 9.394/96, Resolutions, Opinions, Decrees, among others that make up the legal frameworks. As data collection instruments, interviews were selected, with a script previously prepared by the researcher, with the teachers of the third years and pedagogical coordinator responsible for the Initial Years in the periods of 2015 and 2016 and application of evaluative activities in the classes of third years of Elementary School, considering this as the last year of the literacy cycle. Content analysis was used as a methodology since, according to studies by Bardin (1977), it is possible to critically analyze, in a wide way, both the speeches and the meanings of the objects that make up the said research. After analyzing the data, it is concluded that there is a discontinuity in public education policies, referring to the difficulty of implementing the legislation, including in the case presented here, mainly due to the limited resources for the creation of pedagogical support in schools, taking into account the Continued Progression. However, there is a commitment on the part of the teachers to try to fill the gaps of the students who arrive at the third years with learning difficulties and the researched school seeks the interlocution with the community in the search to meet the needs of the students.